Almost γ-continuous functions - F. Cammaroto; T. Noiri (International Journal of Mathematics and Mathematical Sciences)
In this paper, a new class of functions called almost γ-continuous is introduced and their several properties are investigated. This new class is also utilized to improve some published results concerning weak continuity [6] and γ-continuity [2].